The Influence of Green Banking Activities on Environmental Performance of Listed Banks on the Indonesia Stock Exchange - Shofia Ainunnisa; Sri Hasnawati; Ernie Hendrawaty (Eduvest - Journal of Universal Studies, 2024)
This study investigates the effect of green banking and green financing on the environmental performance of banks in Indonesia. Green Banking is a banking approach that integrates environmental factors in policies and operations, while green financing is related to environmentally friendly lending. The purpose of this study is to provide an understanding of the concept of Green Banking and its impact on the environmental performance of banks in Indonesia. Similar research has been conducted in several countries, but research in Indonesia is still limited. The results of this study are expected to serve as a basis for banks in implementing better Green Banking practices to achieve sustainable development